Postponing the Day of Reckoning? Examining Contextual Effects on Public Support for Voter Identification Policies1. (10th February 2017) - Udani, Adriano
Abstract : Objective: This study examines the reasons why a majority of Democrats support restrictive voter identification (ID) laws, in spite of such laws clashing with stereotypical Democratic Party interests. Methods: Racial, ethnic, and class demographic data from the 2006 to 2008 American Community Survey of the U.S. Census are merged with the 2008 Cooperative Congressional Election Study. Multilevel models with mixed effects are used to predict support for photo ID laws. Results: Photo ID support is polarized across political sophistication among Democrats in congressional districts with a higher proportion of foreign‐born residents as well as with higher foreign‐born population growth. In contrast, the increasing presence of foreign‐born residents further solidifies support among Republicans, regardless of sophistication. Further analysis reveals that contextual effects of the foreign‐born population specifically affect white partisans and also polarize attitudes across social class. Conclusions: The results suggest that support for restrictive voter ID laws is highest among Republicans and disengaged Democrats, particularly in racially and ethnically diverse areas.